Attentional Modulation of Thalamic Reticular Neurons - McAlonan, Kerry (J Neurosci, 2006)
The major pathway for visual information reaching cerebral cortex is through the lateral geniculate nucleus (LGN) of the thalamus. Acting on this vital relay is another thalamic nucleus, the thalamic reticular nucleus (TRN). This nucleus receives topographically organized collaterals from both thalamus and cortex and sends similarly organized projections back to thalamus. The inputs to the TRN are excitatory, but the output back to the thalamic relay is inhibitory, providing an ideal organization for modulating visual activity during early processing. This functional architecture led Crick in 1984 to hypothesize that TRN serves to direct a searchlight of attention to different regions of the topographic map; however, despite the substantial influence of this hypothesis, the activity of TRN neurons has never been determined during an attention task. We have determined the nature of the response of visual TRN neurons in awake monkeys, and the modulation of that response as the monkeys shifted attention between visual and auditory stimuli. Visual TRN neurons had a strong (194 spikes/s) and fast (25 ms latency) transient increase of activity to spots of light falling in their receptive fields, as well as high background firing rate (45 spikes/s). When attention shifted to the spots of light, the amplitude of the transient visual response typically increased, whereas other neuronal response characteristics remained unchanged. Thus, as predicted previously, TRN activity is modified by shifts of visual attention, and these attentional changes could influence visual processing in LGN via the inhibitory connections back to the thalamus.